A tris(benzyltriazolemethyl)amine-based cage as a CuAAC ligand tolerant to exogeneous bulky nucleophiles. Issue 18 (3rd February 2021) - Qiu, Gege; Nava, Paola; Martinez, Alexandre; Colomban, Cédric
Abstract : The canonical CuAAC–ligand TBTA was capped with a bowl-shaped unit yielding the cage Hm-TBTA . The shielded structure does not suffer from product inhibition effect and is remarkably tolerant to the biological CuAAC-inhibitor Glutathione. Abstract : The archetypal tris(benzyltriazolemethyl)amine (TBTA) ligand was equipped with a bowl-shaped cap in the cage Hm-TBTA. Hm-TBTA accelerates CuAAC reactions without suffering from product inhibition. Furthermore, this shielded ligand efficiently protects the copper center from deactivation by the Cu I –chelator glutathione, opening the way to novel approaches for efficient CuAAC reactions in complex media.